Flame-resistant odorless nano phenolic aldehyde plate

By modifying the phenolic foam board composite carbon fiber and electrostatically spraying silica, the lack of performance of traditional phenolic foam materials in high compression, high heat insulation and flame resistance is solved, and heat resistance, high flame retardant and compressive resistance are achieved. The effect improves the overall performance of the material.

CN119320513AActive Publication Date: 2025-01-17JIANGSU CANGGU CONSTR ENG CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411207123.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-29
Publication Date
2025-01-17
Estimated Expiration
2043-12-29

AI Technical Summary

Technical Problem

The performance of traditional phenolic foam materials in high compression resistance, high heat insulation and flame resistance is difficult to meet the needs of industries such as aerospace, transportation, etc., and has shortcomings such as low strength and smoldering, which affects its application.

Method used

The modified phenolic foam board is used to combine carbon fiber and make flame-resistant and odorless nanophenolic boards by electrostatic spraying of silica. The boron produced by reacting para-hydroxybenzene, formaldehyde and 3-methoxy-4-methylphenylboric acid Phenolic resin forms boron-oxyboron bond connection structure, combines ultrasonic-magnetic field-assisted microfluidic spinning and dual heating technology to enhance fiber strength, and improve structural roughness through microwave radiation, and finally enhance flame retardant effect by electrostatic spraying of silica .

Benefits of technology

It achieves the effects of heat resistance, high flame retardant and compressive resistance, improves the mechanical strength and flame retardant properties of the material, avoids smoldering, and meets the requirements for the use of high-performance materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a flame-resistant odorless nano phenolic aldehyde plate, and relates to the technical field of phenolic aldehyde plates. According to the invention, p-hydroxybenzophenone, formaldehyde and 3-methoxy-4-methylphenylboronic acid are subjected to a reaction to generate boron phenolic resin, a stable and compact boron carbide layer can be formed in a high-temperature environment, and heat-resistant and high-flame-retardant effects are realized; then, an epoxy structure is introduced into the boron phenolic resin, a high-polymerization net-shaped structure is generated in a matrix, and the compression resistance and flame retardance of the board are improved; melamine and polyacrylonitrile are subjected to ultrasonic-magnetic field assisted microfluidic spinning and dual heating to prepare carbon fibers, a foam board can be indirectly enhanced, then microwave radiation is utilized to form mechanical occlusion between the fibers and resin, then silicon dioxide is sprayed on the two faces of the board through static electricity, and the flame retardant effect of the board is further enhanced. The phenolic aldehyde plate prepared by the invention has the effects of flame retardance and compression resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of phenolic plates, in particular to a flame-resistant and odorless nano-phenolic plate. Background Art

[0002] With the continuous research and development of polymer materials, traditional building materials used in daily life are gradually being replaced by polymer materials. Among them, polymer foam materials have excellent properties such as light weight, shock absorption, and heat insulation due to the large number of micron-sized gas bubbles distributed inside the materials. At present, with the rapid development of aerospace, transportation, construction and other industries, the demand for foam materials in terms of high pressure resistance, high heat insulation, and flame resistance is increasing day by day, and the performance of traditional foaming materials is difficult to meet their use requirements, so it is necessary to modify and optimize polymer foam materials. Among them, phenolic resin has the characteristics of highly cross-linked structure, which can give the material excellent heat resistance and chemical resistance, and also ensure mechanical strength and workpiece dimensional stability. At the same time, it also maintains its own excellent flame retardancy, so it is used in various engineering fields, widely distributed in daily production, and even in military industry and aerospace, mainly used as casting, friction materials, heat-resistant materials, adhesives and substrate coatings, etc.; but when phenolic is made into foam material, although it can work for a long time in an environment of 150°C and has the effect of being difficult to burn and self-extinguishing when burned by flames, it has the disadvantages of low strength and smoldering, which affect its application, so it is particularly important to invent a new phenolic foam material. Summary of the invention

[0003] The purpose of the present invention is to provide a flame retardant and odorless nano-phenolic board and a preparation method thereof, so as to solve the problems existing in the prior art.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a flame retardant and odorless nano-phenolic board, which is made by composite carbon fiber with modified phenolic foam board and then electrostatically spraying silicon dioxide.

[0005] Furthermore, the modified phenolic foam board is prepared by reacting boron phenolic resin prepared from p-hydroxybenzophenone, formaldehyde and 3-methoxy-4-methylphenylboric acid with epichlorohydrin.

[0006] Furthermore, the carbon fiber is made from polyacrylonitrile through ultrasound-magnetic field assisted microfluidic spinning, double heating and other steps.

[0007] Furthermore, a method for preparing a flame-retardant and odorless nano-phenolic board comprises the following preparation steps: (1) 37 wt% formaldehyde aqueous solution and p-hydroxybenzophenone were mixed in a mass ratio of 13:17-17:25, stirred evenly, and then 30 wt% sodium hydroxide aqueous solution (2-3 times the mass of p-hydroxybenzophenone) was added, the temperature was raised to 55-70°C, stirred at 70-100 rpm for 1.5-3 h, cooled to 40-50°C, 3-methoxy-4-methylphenylboronic acid (1-1.5 times the mass of p-hydroxybenzophenone) and methanol (0.4-0.6 times the mass of p-hydroxybenzophenone) were added, the temperature was raised to 65-75°C, reacted for 2-3 h, cooled to 40-50°C again, and 45 wt% sodium hydroxide aqueous solution was added until the solution pH was 8-9, 3 Distill at 5-40°C and 800-1000Pa for 1-3h, then add formic acid until the pH value of the solution is 6.5-7, add epichlorohydrin with a mass of 1.5-3 times that of p-hydroxybenzophenone and tetrabutylammonium bromide with a mass of 0.02-0.04 times that of p-hydroxybenzophenone, raise the temperature to 75-85°C, add sodium hydroxide with a mass of 0.25-0.35 times that of p-hydroxybenzophenone in 4 portions within 60-90min of reaction, continue the reaction for 2.5-4h, filter, take the solid, wash it with deionized water at 50°C for 3-5 times, distill at 10-20°C and 800-1000Pa for 1-3h to obtain a modified phenolic resin; (2) placing the modified phenolic resin in an oil bath at 80°C, stirring at 30-60 rpm for 0.5-1.5 h, adding Tween-80 and n-pentane, stirring at 70-100 rpm for 20-40 min, adding 40 wt% aqueous sulfuric acid solution and p-toluenesulfonic acid, continuing to stir for 1-3 min, pouring into a mold, standing for 60-80 min, demolding, aging at 50-80°C for 8-12 h, and then irradiating with microwaves to obtain a modified phenolic foam board; (3) Mix melamine and 60°C N,N-dimethylformamide in a mass ratio of 0.5:20-1:23, stir at 70-100 rpm for 1.5-3 h, add polyacrylonitrile with a molecular weight of 81,000, which is 4-8 times the mass of melamine, and continue stirring for 10-14 h to obtain a spinning solution, and then perform ultrasound-magnetic field-assisted microfluidic spinning, and dry at 65-75°C for 10-14 h to obtain spun fibers; (4) doubly heating the spun fibers, cooling them, and then covering them on a modified phenolic foam board to obtain a carbon fiber composite modified phenolic foam board; (5) The silica precursor liquid was electrostatically sprayed on both sides of the carbon fiber composite modified phenolic foam board. The spraying process parameters were: voltage 15-25 kV, receiving distance 10-20 cm, flow rate 3 mL / h, and drying at 40-60 °C for 4-6 h to obtain a flame retardant and odorless nano-phenolic board.

[0008] Furthermore, the microwave radiation in step (2) has a wave source of 2400-2500 MHz continuous wave, an output power of 50-70 W, and a duration of 1.5-3 min.

[0009] Furthermore, in step (2), the mass ratio of the modified phenolic resin, Tween-80, n-pentane, 40 wt% aqueous sulfuric acid solution, and p-toluenesulfonic acid is 35:4:8:20:20-45:8:16:30:30.

[0010] Furthermore, the process parameters of the ultrasound-magnetic field assisted microfluidic spinning in step (3) are: extrusion pump propulsion rate 0.3 mL / h, receiving device rotation motor speed 400 r / min, stepper translation motor frequency 6000 Hz, ultrasonic frequency 21 kHz, vibration power 1000 W, vibration time 80 min, magnetic field strength 0.3 T.

[0011] Furthermore, the conditions for the double heating in step (4) are as follows: the first heating time is 1-2 hours, the temperature is 1250-1350°C; the second heating time is 1-3 minutes, the temperature is 150-200°C, the wave source is 2400-2500MHz continuous wave, and the output power is 80-100W.

[0012] Furthermore, the preparation method of the silicon dioxide precursor solution in step (5) is: tetraethyl orthosilicate, acetone, and 1 wt% acetic acid aqueous solution are mixed in a mass ratio of 3:0.8:1.5 to 5:1.2:2.5.

[0013] Furthermore, the electrostatic spraying in step (5) is performed in a nitric acid solution environment with a concentration of 10 mol / L and a temperature of 50-60°C.

[0014] Compared with the prior art, the beneficial effects achieved by the present invention are: The board of the invention is prepared by composite carbon fiber with modified phenolic foam board and then electrostatically spraying microcapsule flame retardant to achieve flame retardant and compression resistance effects.

[0015] Firstly, the boron phenolic resin is generated by the reaction of p-hydroxybenzophenone, formaldehyde and 3-methoxy-4-methylphenylboronic acid. The boron element in the boron phenolic resin can block the easily oxidized phenolic hydroxyl groups under high temperature environment, cross-link itself to form a structure connected by boron oxygen boron bonds, thereby reducing the distance between the benzene rings and greatly improving the thermal performance of the system. It can also capture free phenolic hydroxyl groups and adhere to the surface of the substrate to form a stable and dense boron carbide layer to isolate the air. In the later stage of weightlessness, it still maintains a high residual carbon rate, thereby achieving heat resistance and high flame retardancy. Then, the hydroxyl group of p-hydroxybenzophenone is cyclic etherified and an epoxy structure is introduced to produce a polymer network structure with a high degree of cross-linking. With the addition of a large number of benzene rings, the mechanical strength of the resin is improved, thereby achieving a compressive effect and enhancing the flame retardant performance of the board.

[0016] Secondly, melamine and polyacrylonitrile are used to prepare nanofiber membranes through ultrasound-magnetic field assisted microfluidic spinning, in which ultrasonic vibration enhances the peristalsis of molecular chains in the spinning solution, thereby disentangling them and reducing the interaction force. With the assistance of the magnetic field, the orientation of the molecular chains is arranged consistently, and the order of the prepared fibers is improved, thereby improving the fiber strength and indirectly enhancing the compressive resistance of the foam board. The fibers are then carbonized by double heating, thereby enhancing the compressive resistance of the matrix. Next, microwave radiation is used to increase the roughness of the carbon fiber membrane and the matrix, forming an uneven concave-convex structure, thereby forming a mechanical bite between the fiber and the resin. Then, silica is sprayed on both sides of the board by electrostatics, one side is filled in the foam pores, and the other side is placed in an acidic water mist environment during the electrostatic spraying process, which stimulates the oxygen-containing groups of silica and carbon fiber, and then the silica microcapsule flame retardant is grafted on the carbon fiber by hydrogen bonding, further enhancing the flame retardant effect of the board, which is more conducive to preventing the smoldering of boron phenolic formaldehyde. DETAILED DESCRIPTION

[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0018] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the flame retardant and odorless nano-phenolic board prepared in the following examples are as follows: Compression resistance: Take the embodiment and comparative example of the same size and perform the compressive strength test with reference to GB / T5486.

[0019] Thermal insulation: Take the embodiment and comparative example of the same size and conduct thermal conductivity test with reference to GB / T10294.

[0020] Flame retardancy: The embodiment and the comparative example of the same size were taken and subjected to UL94 horizontal and vertical burning test and material LOI test according to GB / T2408 and GB / T2406.2 standards.

[0021] Example 1 (1) 37 wt% formaldehyde aqueous solution and p-hydroxybenzophenone were mixed in a mass ratio of 13:17, stirred evenly, and then 30 wt% sodium hydroxide aqueous solution (2 times the mass of p-hydroxybenzophenone) was added, the temperature was raised to 55°C, stirred at 70 rpm for 1.5 h, cooled to 40°C, 3-methoxy-4-methylphenylboronic acid (1 times the mass of p-hydroxybenzophenone) and methanol (0.4 times the mass of p-hydroxybenzophenone) were added, the temperature was raised to 65°C, reacted for 2 h, cooled to 40°C again, and 45 wt% sodium hydroxide aqueous solution was added until the solution pH was 5. 8. Distill at 35°C and 800Pa for 1h, then add formic acid until the solution pH is 6.5, add epichlorohydrin (1.5 times the mass of p-hydroxybenzophenone) and tetrabutylammonium bromide (0.02 times the mass of p-hydroxybenzophenone), raise the temperature to 75°C, add sodium hydroxide (0.25 times the mass of p-hydroxybenzophenone) in 4 portions within 60min of reaction, continue the reaction for 2.5h, filter, take the solid, wash it 3 times with deionized water at 50°C, distill at 10°C and 800Pa for 1h to obtain modified phenolic resin; (2) placing the modified phenolic resin in an oil bath at 80°C, stirring at 30 rpm for 0.5 h, adding Tween-80 and n-pentane, stirring at 70 rpm for 20 min, adding 40 wt% sulfuric acid aqueous solution and p-toluenesulfonic acid, continuing to stir for 1 min, pouring into a mold, standing for 60 min, demolding, aging at 50°C for 8 h, and then irradiating with microwaves with a wave source of 2400 MHz continuous wave and an output power of 50 W for 1.5 min to obtain a modified phenolic foam board; the mass ratio of the modified phenolic resin, Tween-80, n-pentane, 40 wt% sulfuric acid aqueous solution, and p-toluenesulfonic acid is 35:4:8:20:20; (3) Melamine and 60°C N,N-dimethylformamide were mixed in a mass ratio of 0.5:20, stirred at 70-100 rpm for 1.5 h, polyacrylonitrile with a molecular weight of 81,000, which was 4 times the mass of melamine, was added, and the stirring was continued for 10 h to obtain a spinning solution, and then ultrasound-magnetic field-assisted microfluidic spinning was performed. The spinning process parameters were: extrusion pump propulsion rate 0.3 mL / h, receiving device rotation motor speed 400 r / min, stepper translation motor frequency 6000 Hz, ultrasonic frequency 21 kHz, vibration power 1000 W, vibration time 80 min, magnetic field intensity 0.3 T, and dried at 65°C for 10 h to obtain spun fibers; (4) The spun fiber is double heated; the first heating time is 1 hour and the temperature is 1250°C; the second heating time is 1 minute and the temperature is 150°C, the microwave radiation source is 2400MHz continuous wave, the output power is 80W, and after cooling, it is covered on the modified phenolic foam board to obtain a carbon fiber composite modified phenolic foam board; (5) Tetraethyl orthosilicate, acetone, and 1 wt% acetic acid aqueous solution were mixed in a mass ratio of 3:0.8:1.5 to obtain a silica precursor solution; in an environment of a 10 mol / L nitric acid solution, the silica precursor solution was electrostatically sprayed on both sides of a carbon fiber composite modified phenolic foam board at 50°C, and the spraying process parameters were: voltage 15 kV, receiving distance 10 cm, flow rate 3 mL / h, and drying at 40°C for 4 h to obtain a flame retardant and odorless nano-phenolic board.

[0022] Example 2 (1) 37 wt% formaldehyde aqueous solution and p-hydroxybenzophenone were mixed in a mass ratio of 15:21, stirred evenly, and then 30 wt% sodium hydroxide aqueous solution (2.5 times the mass of p-hydroxybenzophenone) was added, the temperature was raised to 62°C, stirred at 85 rpm for 2.5 h, cooled to 45°C, 3-methoxy-4-methylphenylboronic acid (1.3 times the mass of p-hydroxybenzophenone) and methanol (0.5 times the mass of p-hydroxybenzophenone) were added, the temperature was raised to 70°C, reacted for 2.5 h, cooled to 45°C again, and 45 wt% sodium hydroxide aqueous solution was added until the solution was molten. H is 8.5, distill at 38°C and 900Pa for 2h, then add formic acid until the solution pH is 6.8, add epichlorohydrin 2.3 times the mass of p-hydroxybenzophenone and tetrabutylammonium bromide 0.03 times the mass of p-hydroxybenzophenone, heat to 80°C, add sodium hydroxide 0.3 times the mass of p-hydroxybenzophenone in 4 times within 85min of reaction, continue to react for 3.5h, filter, take the solid, wash 4 times with 50°C deionized water, distill at 15°C and 900Pa for 1.5h to obtain modified phenolic resin; (2) placing the modified phenolic resin in an oil bath at 80°C, stirring at 45 rpm for 1 hour, adding Tween-80 and n-pentane, stirring at 85 rpm for 30 minutes, adding 40 wt% sulfuric acid aqueous solution and p-toluenesulfonic acid, continuing to stir for 2 minutes, pouring into a mold, standing for 70 minutes, demolding, aging at 65°C for 10 hours, and then irradiating with microwaves with a wave source of 2450 MHz continuous wave and an output power of 60 W for 2.5 minutes to obtain a modified phenolic foam board; the mass ratio of the modified phenolic resin, Tween-80, n-pentane, 40 wt% sulfuric acid aqueous solution, and p-toluenesulfonic acid is 40:6:12:25:25; (3) Melamine and 60°C N,N-dimethylformamide were mixed in a mass ratio of 0.75:21.5, stirred at 85 rpm for 2.5 h, polyacrylonitrile with a molecular weight of 81000, which was 6 times the mass of melamine, was added, and the stirring was continued for 12 h to obtain a spinning solution, and then ultrasound-magnetic field-assisted microfluidic spinning was performed. The spinning process parameters were: extrusion pump propulsion rate 0.3 mL / h, receiving device rotation motor speed 400 r / min, stepper translation motor frequency 6000 Hz, ultrasonic frequency 21 kHz, vibration power 1000 W, vibration time 80 min, magnetic field intensity 0.3 T, and dried at 70°C for 12 h to obtain spun fibers; (4) The spun fiber is double heated; the first heating time is 1.5 hours and the temperature is 1300°C; the second heating time is 1.5 minutes and the temperature is 175°C, the microwave radiation source is 2450MHz continuous wave, the output power is 90W, and after cooling, it is covered on the modified phenolic foam board to obtain a carbon fiber composite modified phenolic foam board; (5) Tetraethyl orthosilicate, acetone, and 1 wt% acetic acid aqueous solution were mixed in a mass ratio of 4:1:2 to obtain a silica precursor solution; in an environment of a 10 mol / L nitric acid solution, the silica precursor solution was electrostatically sprayed on both sides of a carbon fiber composite modified phenolic foam board at 55°C, and the spraying process parameters were: voltage 20 kV, receiving distance 15 cm, flow rate 3 mL / h, and dried at 50°C for 5 h to obtain a flame retardant and odorless nano-phenolic board.

[0023] Example 3 (1) 37 wt% formaldehyde aqueous solution and p-hydroxybenzophenone were mixed in a mass ratio of 17:25, stirred evenly, and then 30 wt% sodium hydroxide aqueous solution (3 times the mass of p-hydroxybenzophenone) was added, the temperature was raised to 70°C, stirred at 100 rpm for 3 h, cooled to 50°C, 1.5 times the mass of p-hydroxybenzophenone 3-methoxy-4-methylphenylboronic acid and 0.6 times the mass of p-hydroxybenzophenone methanol were added, the temperature was raised to 75°C, reacted for 3 h, cooled to 50°C again, and 45 wt% sodium hydroxide aqueous solution was added to the solution. The pH value is 9, distilled at 40°C and 1000Pa for 3h, then formic acid is added until the solution pH value is 7, epichlorohydrin 3 times the mass of p-hydroxybenzophenone and tetrabutylammonium bromide 0.04 times the mass of p-hydroxybenzophenone are added, the temperature is raised to 85°C, and within 90min of reaction, sodium hydroxide 0.35 times the mass of p-hydroxybenzophenone is added in 4 times, the reaction is continued for 4h, filtered, the solid is taken, washed with 50°C deionized water 5 times, and distilled at 20°C and 1000Pa for 3h to obtain modified phenolic resin; (2) placing the modified phenolic resin in an oil bath at 80°C, stirring at 60 rpm for 1.5 h, adding Tween-80 and n-pentane, stirring at 100 rpm for 40 min, adding 40 wt% sulfuric acid aqueous solution and p-toluenesulfonic acid, continuing to stir for 3 min, pouring into a mold, standing for 80 min, demolding, aging at 80°C for 12 h, and then irradiating with microwaves with a wave source of 2500 MHz continuous wave and an output power of 70 W for 3 min to obtain a modified phenolic foam board; the mass ratio of the modified phenolic resin, Tween-80, n-pentane, 40 wt% sulfuric acid aqueous solution, and p-toluenesulfonic acid is 45:8:16:30:30; (3) Melamine and 60°C N,N-dimethylformamide were mixed in a mass ratio of 1:23, stirred at 100 rpm for 3 h, polyacrylonitrile with a molecular weight of 81000, which was 8 times the mass of melamine, was added, and the stirring was continued for 14 h to obtain a spinning solution, and then ultrasound-magnetic field-assisted microfluidic spinning was performed. The spinning process parameters were: extrusion pump propulsion rate 0.3 mL / h, receiving device rotation motor speed 400 r / min, stepper translation motor frequency 6000 Hz, ultrasonic frequency 21 kHz, vibration power 1000 W, vibration time 80 min, magnetic field intensity 0.3 T, and dried at 75°C for 14 h to obtain spun fibers; (4) The spun fiber is double heated; the first heating time is 2 hours and the temperature is 1350°C; the second heating time is 3 minutes and the temperature is 200°C, the microwave radiation source is 2500MHz continuous wave, the output power is 100W, and after cooling, it is covered on the modified phenolic foam board to obtain a carbon fiber composite modified phenolic foam board; (5) Tetraethyl orthosilicate, acetone, and 1 wt% acetic acid aqueous solution were mixed in a mass ratio of 5:1.2:2.5 to obtain a silica precursor solution; in an environment of a 10 mol / L nitric acid solution, the silica precursor solution was electrostatically sprayed on both sides of a carbon fiber composite modified phenolic foam board at 60°C. The spraying process parameters were: voltage 25 kV, receiving distance 20 cm, flow rate 3 mL / h, and drying at 60°C for 6 h to obtain a flame retardant and odorless nano-phenolic board.

[0024] Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that step (1) is different. Step (1) is changed to: 37 wt% formaldehyde aqueous solution and p-hydroxybenzophenone are mixed in a mass ratio of 15:21, stirred evenly, 30 wt% sodium hydroxide aqueous solution of 2.5 times the mass of p-hydroxybenzophenone is added, the temperature is raised to 62°C, stirred at 85 rpm for 2.5 h, cooled to 45°C, methanol of 0.5 times the mass of p-hydroxybenzophenone is added, the temperature is raised to 70°C, reacted for 2.5 h, cooled to 45°C again, and 45 wt% sodium hydroxide aqueous solution is added until the solution pH is 8.5 , distill at 38°C and a pressure of 900Pa for 2h, then add formic acid until the solution pH is 6.8, add 2.3 times the mass of epichlorohydrin and 0.03 times the mass of tetrabutylammonium bromide of p-hydroxybenzophenone, raise the temperature to 80°C, add 0.3 times the mass of p-hydroxybenzophenone sodium hydroxide in 4 times within 85min of the reaction, continue the reaction for 3.5h, filter, take the solid, wash 4 times with 50°C deionized water, and distill at 15°C and a pressure of 900Pa for 1.5h to obtain a modified phenolic resin; the remaining steps are the same as those in Example 2.

[0025] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that step (1) is different. Step (1) is changed to: 37 wt % formaldehyde aqueous solution and p-hydroxybenzophenone are mixed in a mass ratio of 15:21, stirred evenly, and then 30 wt % sodium hydroxide aqueous solution (2.5 times the mass of p-hydroxybenzophenone) is added, the temperature is raised to 62° C., stirred at 85 rpm for 2.5 h, cooled to 45° C., 3-methoxy-4-methylphenylboronic acid (1.3 times the mass of p-hydroxybenzophenone) is added, the temperature is raised to 70° C., reacted for 2.5 h, cooled to 45° C. again, 45 wt % sodium hydroxide aqueous solution is added until the solution pH is 8.5, and distilled at 38° C. and a pressure of 900 Pa for 2 h to obtain a modified phenolic resin; the remaining steps are the same as those in Example 2.

[0026] Comparative Example 3 The difference between Comparative Example 3 and Example 2 is that step (3) and step (4) are omitted; the remaining steps are the same as those of Example 2.

[0027] Comparative Example 4 The difference between Comparative Example 4 and Example 2 is that there is no step (5); the remaining steps are the same as Example 2.

[0028] Comparative Example 5 The difference between Comparative Example 5 and Example 2 is that there is no step (3), step (4) and step (5), and step (1) is changed to: 37wt% formaldehyde aqueous solution and p-hydroxyphenone are mixed in a mass ratio of 15:21, stirred evenly, and then 30wt% sodium hydroxide aqueous solution (2.5 times the mass of p-hydroxyphenone) is added, the temperature is raised to 62°C, stirred at 85rpm for 2.5h, cooled to 45°C, and distilled at 38°C and a pressure of 900Pa for 2h to obtain phenolic resin; the remaining steps are the same as those in Example 2.

[0029] Effect example Table 1 below shows the performance analysis results of the flame retardant and odorless nano-phenolic board materials of Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.

[0030] Table 1 From the comparison of the test data of the embodiment and the comparative example, it can be found that the boron phenolic resin generated by the reaction of p-hydroxybenzophenone, formaldehyde and 3-methoxy-4-methylphenylboronic acid can block the easily oxidized phenolic hydroxyl groups under high temperature environment, so that a stable and dense boron carbide layer is formed on the surface of the substrate, thereby isolating the air and achieving the effects of heat resistance and high flame retardancy; then, an epoxy structure is introduced into the boron phenolic resin to produce a polymeric network structure, thereby improving the mechanical strength of the resin; carbon fibers prepared by using melamine and polyacrylonitrile through ultrasonic-magnetic field-assisted microfluidic spinning and double heating can indirectly enhance the compressive resistance of the foam board, and then microwave radiation is used to increase the roughness of the carbon fiber film and the substrate, so that a mechanical bite is formed between the fiber and the resin, and then silicon dioxide is sprayed on both sides of the board by electrostatics, thereby enhancing the flame retardant effect of the board.

[0031] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A flame retardant and odorless nano-phenolic board, characterized in that: The flame retardant and odorless nano-phenolic board is prepared by composite carbon fiber with a modified phenolic foam board and then electrostatically spraying silicon dioxide. The method for preparing the flame retardant and odorless nano-phenolic board comprises the following preparation steps: (1) 37 wt% formaldehyde aqueous solution and p-hydroxybenzophenone were mixed in a mass ratio of 15:21, stirred evenly, and then 30 wt% sodium hydroxide aqueous solution (2.5 times the mass of p-hydroxybenzophenone) was added, the temperature was raised to 62°C, stirred at 85 rpm for 2.5 h, cooled to 45°C, 3-methoxy-4-methylphenylboronic acid (1.3 times the mass of p-hydroxybenzophenone) and methanol (0.5 times the mass of p-hydroxybenzophenone) were added, the temperature was raised to 70°C, reacted for 2.5 h, cooled to 45°C again, and 45 wt% sodium hydroxide aqueous solution was added until the solution was molten. H is 8.5, distill at 38°C and 900Pa for 2h, then add formic acid until the solution pH is 6.8, add epichlorohydrin 2.3 times the mass of p-hydroxybenzophenone and tetrabutylammonium bromide 0.03 times the mass of p-hydroxybenzophenone, heat to 80°C, add sodium hydroxide 0.3 times the mass of p-hydroxybenzophenone in 4 times within 85min of reaction, continue to react for 3.5h, filter, take the solid, wash 4 times with 50°C deionized water, distill at 15°C and 900Pa for 1.5h to obtain modified phenolic resin; (2) placing the modified phenolic resin in an oil bath at 80°C, stirring at 45 rpm for 1 hour, adding Tween-80 and n-pentane, stirring at 85 rpm for 30 minutes, adding 40 wt% sulfuric acid aqueous solution and p-toluenesulfonic acid, continuing to stir for 2 minutes, pouring into a mold, standing for 70 minutes, demolding, aging at 65°C for 10 hours, and then irradiating with microwaves with a wave source of 2450 MHz continuous wave and an output power of 60 W for 2.5 minutes to obtain a modified phenolic foam board; the mass ratio of the modified phenolic resin, Tween-80, n-pentane, 40 wt% sulfuric acid aqueous solution, and p-toluenesulfonic acid is 40:6:12:25:25; (3) Melamine and 60°C N,N-dimethylformamide were mixed in a mass ratio of 0.75:21.5, stirred at 85 rpm for 2.5 h, polyacrylonitrile with a molecular weight of 81000, which was 6 times the mass of melamine, was added, and the stirring was continued for 12 h to obtain a spinning solution, and then ultrasound-magnetic field-assisted microfluidic spinning was performed. The spinning process parameters were: extrusion pump propulsion rate 0.3 mL / h, receiving device rotation motor speed 400 r / min, stepper translation motor frequency 6000 Hz, ultrasonic frequency 21 kHz, vibration power 1000 W, vibration time 80 min, magnetic field intensity 0.3 T, and dried at 70°C for 12 h to obtain spun fibers; (4) The spun fiber is double heated; the first heating time is 1.5 hours and the temperature is 1300°C; the second heating time is 1.5 minutes and the temperature is 175°C, the microwave radiation source is 2450MHz continuous wave, the output power is 90W, and after cooling, it is covered on the modified phenolic foam board to obtain a carbon fiber composite modified phenolic foam board; (5) Tetraethyl orthosilicate, acetone, and 1 wt% acetic acid aqueous solution were mixed in a mass ratio of 4:1:2 to obtain a silica precursor solution; in an environment of a 10 mol / L nitric acid solution, the silica precursor solution was electrostatically sprayed on both sides of a carbon fiber composite modified phenolic foam board at 55°C, and the spraying process parameters were: voltage 20 kV, receiving distance 15 cm, flow rate 3 mL / h, and dried at 50°C for 5 h to obtain a flame retardant and odorless nano-phenolic board.

Citation Information

Patent Citations

  • Light flame-retardant phenolic foam material and preparation method thereof

    CN108102291A

  • Preparation method of melamine / polyurethane toughened phenolic foam

    CN108467567A

  • High-stability friction-resistant brake pad and production process of high-stability friction-resistant brake pad

    CN111779782A

  • High-temperature-resistant thermosensitive medical film with stable imaging and preparation process of high-temperature-resistant thermosensitive medical film

    CN116890555A

  • Modified phenolic foams

    US4525492A